1975
DOI: 10.1113/jphysiol.1975.sp011052
|View full text |Cite
|
Sign up to set email alerts
|

Drinking by dogs during and after running.

Abstract: SUMMARY1. Drinking by dogs has been studied during and after running on a treadmill, and compared with the drinking produced by NaCi given by stomach tube or intravenously.2. When water was offered with a delay of more than 5 min after the end of a run producing loss of 30-90 g water by panting, the drinking was similar to that produced by NaCl, assuming that loss of 100 g water produces the same increase in plasma sodium as 15 m-mole NaCl. It is thus possible to explain drinking with a delay after the run as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…O'Connor (1982) has presented the factors which determine drinking and urine volume: in dogs doses of water of 100 ml given by stomach tube inhibit drinking (O'Connor & Potts, 1969;O'Connor, 1975); larger doses of water produce an increased volume of dilute urine (water diuresis). In the double-feeding experiments of this paper, retention of 500 g or more of water neither stopped drinking nor produced water diuresis.…”
Section: Resultsmentioning
confidence: 99%
“…O'Connor (1982) has presented the factors which determine drinking and urine volume: in dogs doses of water of 100 ml given by stomach tube inhibit drinking (O'Connor & Potts, 1969;O'Connor, 1975); larger doses of water produce an increased volume of dilute urine (water diuresis). In the double-feeding experiments of this paper, retention of 500 g or more of water neither stopped drinking nor produced water diuresis.…”
Section: Resultsmentioning
confidence: 99%
“…Water deposited in cells or lost in the urine is effectively a deprivation of the rest of the body by this amount of water. Dehydration of 50 g is capable of causing drinking in dogs at rest [O'Connor, 1975], the mechanism presumably being increase in the osmotic pressure or Na concentration of the blood. This seems a likely explanation ofpost-prandial drinking in the dog.…”
Section: Resultsmentioning
confidence: 99%
“…This form of drinking was reproduced by O'Connor [1975] in experiments in which drinking was studied during the controlled activity of running on a treadmill. O'Connor [1975] concluded that activity immediately caused both panting and drinking so that the water lost by evaporation during panting was promptly replaced and dehydration thus avoided.As well as drinking during activity, O'Connor and Potts [1969] also recorded drinking at night after the daily meal eaten at 17.00 and when the dogs were quiet in their cages. Between 17.00 and 03.00 the dogs often took one or more drinks, usually larger than 50 ml, which formed a variable but considerable contribution to the daily water intake.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Central thermally sensitive elements in the hypothalamus may also have been involved in drinking since Andersson, Gale & Sundsten (1962) found that changing hypothalamic temperature usually affected drinking even in the absence of dehydration in the goat. In the dog, O'Connor (1975O'Connor ( , 1977 has demonstrated that exercise or panting under the influence of radiant heat also produced an increase in drinking even before dehydration. O'Connor suggested that raised skin temperature during radiant heating itself is a direct stimulus to drinking.…”
Section: Introductionmentioning
confidence: 99%